Chemical variables - stream from Tarfalajokk, Water sample A - Tarfala Research Station (Stockholm University, 2025)
Manual grab samples from the stream for chemical analysis are taken on a biweekly basis during ice-free conditions, and on a monthly basis in the presence of stream ice.
Tarfala Research Station (2025). Chemical variables - stream from Tarfalajokk, Water sample A, 2017-05-20–2017-09-12 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/p4-X7JvwIiu82xh4UDwycqbn
Keywords: Tarfala Research Station; Stream; Time instant; Time instant; pH; pH; Electrical conductivity; Electrical conductivity; Dissolved organic carbon; Dissolved organic carbon; Total nitrogen; Total nitrogen; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Nitrite-N/Nitrate-N; Nitrite-N/Nitrate-N; Sulphate-S; Sulphate-S; Fluorine; Fluorine; Chlorine; Chlorine; Proportion Oxygen-18 in Water; Proportion Oxygen-18 in Water; Proportion Deuterium in Water; Proportion Deuterium in Water; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap